Character Education Strategies in The Millennial Era - Steven S. N. Rogahang (Eduvest - Journal of Universal Studies, 2024)
Character education is becoming an increasingly important aspect in facing moral and ethical challenges in the millennial era which is characterized by social complexity and technological advances. In this context, developing effective character education strategies is a top priority in modern education. This research aims to explore character education strategies that are relevant and effective in facing the dynamics of the millennial era, as well as to analyze their impact on student character formation. The research approach used in this study is literature analysis. Data was obtained through a review of various literature sources, including scientific journals, books and research reports relevant to the theme of character education in the millennial era. The results of the literature analysis show that effective character education strategies in the millennial era include a collaborative approach between schools, families, communities and other institutions, integration of technology in learning, and strengthening traditional values. The collaborative approach ensures consistency and depth in character formation, while the integration of technology enables the delivery of character values in a way that is attractive and relevant to the millennial generation. Strengthening traditional values such as integrity, honesty, empathy and responsibility remains an important foundation in character education in this era.